Interest Rate Elasticity of Residential Housing Prices - Iossifov, Plamen (IMF Working Papers; Working Paper, 2008)
We examine the interest rate elasticity of housing prices, advancingthe empirical literature in two directions. First, we take a commonly used cross-country panel dataset and evaluate the housing price equation using a consistent estimator in the presence of endogenous explanatory variables and a lagged dependent variable. Second, we carry-out a novel analysis of determinants of residential housing prices in a cross-section of countries. Our results show that the short-term interest rate, and hence monetary policy, has a sizable impact on residential housing prices.